PRECIPITATING FACTORS OF HEPATIC ENCEPHALOPATHY: EXPERIENCE AT PAKISTAN INSTITUTE OF MEDICAL SCIENCES ISLAMABAD. - Maqsood, Saad; Saleem, Amer; Iqbal, Adeel; Butt, Javed Aslam (Journal of Ayub Medical College Abbottabad, 2006)
Background: Hepatic encephalopathy is an extra hepatic complication of impaired liver function and is manifested as neuropsychiatric signs and symptoms associated with acute or chronic liver disease in the absence of other neurological disorders. There are numerous factors of hepatic encephalopathy. The main objective of this study was to analyse the precipitating factors of hepatic encephalopathy in cases seen in Pakistan Institute of Medical Sciences Islamabad. Methods: Fifty admitted patients with acute or chronic liver diseases complicating to hepatic encephalopathy were probed into for precipitating factors, based on history, clinical examination and laboratory methods from September 2005 to December 2005. The associated biochemical laboratory data analysis and prognostic stratification through Child's Pugh classification was also done. Results: Infection (44%), gastrointestinal bleeding (38%) and constipation (38%), stood out as the most common factors. Usage of drugs with ammonium salts, tranquilizers and large volume paracentesis were least common factors. Most patients were in grade III (52%), and grade IV (22%), of hepatic encephalopathy. Other common associations were ascites (64%), Child's class C (62%), hyponatremia (50%), low haemoglobin (70%), hepatitis C (62%), and high mortality rate (30%). Conclusion: Infection, gastrointestinal bleeding and constipation being the most important precipitating factors must be prevented and hospital funds, medicines and human efforts should lay emphasis, on these factors to decrease the incidence of hepatic encephalopathy. This also includes effective control measures against rising cases of hepatitis C, as it is the leading cause of liver cirrhosis in Pakistan. Key Words: Hepatic Encephalopathy, Liver cirrhosis, precipitating factors.